A Study on the Relations Between Chinese Government and Private Enterprises on the Course of Internationalization —A Case of Huajian Group - WU, Yiming; CHEN, Siying (Advances in Social Sciences Research Journal, 2019)
The study illustrates the results of a research aimed at exploring the relations between government and private enterprises in the process of Internationalization. Taking Huajian Group as the case study object, the study centers on two issues. The primary issue is to identify how the government–enterprise relations during the case analysis have changed over time；on the other hand, the study focuses on goal orientation of the relations between government and private enterprises on a firm basis. In order to diagnose these problems, qualitative and quantitative methods are used through the whole study. Besides the literature study, a questionnaire and a semi-structure interview are conducted to acquire data and information. In particular, SERVQUAL model is applied for the design and orientation of the government-enterprise relations in support of Internationalization. The results demonstrate that the relations characterized by cooperation and mutual assistance may play a crucial role in the process of Internationalization for Chinese private enterprises. It is suggested that legal aids and guidance from Chinese government are essential for Chinese private enterprises, for it could provide reference for the establishment of an effective relations and clearer positioning of government in a global market.